Peningkatan Kemampuan Penalaran Matematis Siswa melalui Model Realistic Mathematics Education Berbantuan Quiziz: Penelitian - Siti Asiah Rangkuti; Nur Rahmi Rizqi; Yenni Novita Harahap (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the improvement between the Realistic Mathematic Education model and the conventional learning model on students' Mathematical Reasoning abilities with the material of Curved Side Space Buildings. This type of research is quantitative, and the research techniques used in this study are observation, testing, interviews and documentation. Based on the results of data analysis and pretest posttest data hypotheses, the average posttest value of the experimental class can be obtained at 0.738, the average posttest of the Control class is 0.039, so there is an increase in the Realistic Mathematic Education learning model on students' mathematical reasoning abilities using Quiziz. This is evidenced by the results of the t-test obtained tcount> ttable, namely (0.000> 0.05). This means that there is a difference in the average mathematical reasoning ability of students before and after using the Realistic Mathematic Education learning model. The pretest Normality Test shows that the sig. value is 0.993> 0.05. While the pretest Homogeneity test shows a sig. value of 0.395> 0.05. The results of the data analysis test in the form of pre-test data hypothesis testing, showed that both sample classes had the same initial ability regarding students' Mathematical Reasoning abilities.